Pilot study to enhance HIV care using needle exchange-based health services for out-of-treatment injecting drug users. - Altice, Frederick L; Springer, Sandra; Buitrago, Marta; Hunt, David P; Friedland, Gerald H (Journal of urban health : bulletin of the New York Academy of Medicine, 2003)
The introduction of highly active antiretroviral therapy (HAART) has resulted in marked reductions in mortality and acquired immunodeficiency syndrome (AIDS) incidence across all risk groups; however, the proportionate decrease among injecting drug users (IDUs) has been less impressive. Much of the disparity in benefit to IDUs has been a consequence of decreased access to and receipt of potent antiretroviral combinations. Strategies to increase access to and utilization of HAART have included entry into drug treatment and abstinence. Unfortunately, as few as 15%-20% of active drug users in the United States, and in many other countries, are in drug treatment at any one time. We report a pilot project among out-of-drug treatment IDUs infected with human immunodeficiency virus (HIV); HIV therapy was successfully provided to active heroin injectors using the Community Health Care Van (CHCV) at sites of needle exchange. Subjects were willing to initiate, but were not receiving, recommended HIV therapy and were not interested in formal drug treatment. Antiretroviral therapy regimens were selected and linked to heroin injection timing. Weekly visits were scheduled by CHCV staff to assess adverse side effects and encourage adherence. Of the 13 participants, the mean baseline HIV-1 RNA level and CD4 lymphocyte count were 162,369 (log 5.21) copies per milliliter and 265 cells per milliliter, respectively. By 6 months, the proportion whose HIV-1 RNA was below the limits of detection (<400 copies/mL) was 85% (N=11); 77% (N=10) had nondetectable levels by 9 months. By 12 months, 54% (N=7) had a persistently nondetectable viral load, and the net increase in CD4 lymphocyte count was 150 cells per milliliter. As an additional and unintended benefit of this pilot project, 9 (69%) subjects chose to enter drug treatment after achieving a nondetectable viral load. Entry into drug treatment was associated with durability of viral suppression. This small pilot study suggests that health services based on needle exchange may enhance access to HAART among out-of-treatment HIV-infected IDUs. In addition, it demonstrates that this population can benefit from this therapy with the support of a nontraditional, community-based health intervention.
Keywords: Adult; Antiretroviral Therapy, Highly Active; CD4 Lymphocyte Count; Connecticut; Directly Observed Therapy; Ethnic Groups; Female; Heroin Dependence; HIV Infections; HIV-1; Humans; Male; Methadone; Middle Aged; Needle-Exchange Programs; Patient Compliance; Pilot Projects; Substance Abuse, Intravenous; Viral Load